STRATEGIES FOR DEVELOPING THE COMPETITIVENESS OF HOUSEHOLD FOOD-PRODUCT MSMEs IN SOUTH CENTRAL TIMOR REGENCY - Elsiana Brikmar; Doppy Roy Nendissa; Agus A. Nalle (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Micro, small, and medium enterprises (MSMEs) play an important role in national and regional economic growth. Nevertheless, household food-product MSMEs in South Central Timor Regency continue to face various constraints that hinder improvements in competitiveness, including weak financial recordkeeping, limited production technology, low workforce knowledge, limited business capital, suboptimal product quality standardization, and inadequate business legality. This study aims to: (1) identify and analyze the factors affecting the competitiveness of household food-product MSMEs in South Central Timor Regency based on the Porter Diamond Model; (2) formulate alternative strategies for developing the competitiveness of household food-product MSMEs in South Central Timor Regency based on SWOT analysis; and (3) determine the most appropriate priority strategies for developing competitive household food-product MSMEs in South Central Timor Regency using the AHP method. A mixed-methods approach combining qualitative and quantitative approaches in a single study was employed through questionnaires and interviews with 56 MSME respondents (determined using Slovin's formula) and five expert respondents purposively selected based on their competence and experience in developing household food MSMEs in TTS Regency. The Internal Factor Evaluation (IFE) matrix yielded a total score of 2.686, while the External Factor Evaluation (EFE) matrix yielded 2.695, placing TTS MSMEs in Cell V (hold and maintain) of the IE matrix. The SWOT analysis produced nine alternative strategies. The AHP analysis identified business legality as the most influential factor (weight: 0.242), with the highest-priority strategy being to build customer trust through legally compliant products (weight: 0.220). These findings offer practical recommendations for the Local Government, MSME actors, and future research. This study also makes a scholarly contribution by integrating the Porter Diamond Model, SWOT, and the Analytic Hierarchy Process (AHP) in formulating strategies to develop the competitiveness of household food MSMEs, an approach that has rarely been applied in previous studies in South Central Timor Regency.